2007
DOI: 10.1248/cpb.55.658
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Dextromethorphan by Cunninghamella blakesleeana AS 3.153

Abstract: The capability of Cunninghamella blakesleeana AS 3.153 to transform CYP2D6 probe drug dextromethorphan was investigated. Metabolites produced by strain AS 3.153 were detected by liquid chromatography-tandem mass spectrometry (LC-MS n ) and the metabolite dextrorphan was identified by reference to confirm its structure. The yield of dextrorphan produced by C. blakesleeana AS 3.153 was over 90%. Quinidine, a CYP2D6 selective inhibitor, was applied to investigate its effect on biotransformation. The concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…22 In addition to phase I metabolism, C. elegans was also involved in almost all of phase II metabolisms, such as sulfation, glucosylation, and glucuronide formation. 26,49,50 The ability of C. elegans to mimic mammalian metabolism and to perform novel biotransformations would help us reveal the metabolic fates of organic compounds occurring in mammalian liver cells, instead of using live organisms. This microbial system also provides an alternative method for the production of metabolites in large quantities.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…22 In addition to phase I metabolism, C. elegans was also involved in almost all of phase II metabolisms, such as sulfation, glucosylation, and glucuronide formation. 26,49,50 The ability of C. elegans to mimic mammalian metabolism and to perform novel biotransformations would help us reveal the metabolic fates of organic compounds occurring in mammalian liver cells, instead of using live organisms. This microbial system also provides an alternative method for the production of metabolites in large quantities.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Due to the rapid and extensive metabolism of ART in the body [7,8,9], direct study of its metabolites in the body is challenging [10,11,12,13,14]. Significant progresses have been made to predict the drug disposal process, and a series of metabolites have been predicted in previous studies [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the biotransformation of drugs by fungi [11][12][13][14][15][16][17][18][19] and it has been shown that some of these organisms produce mammalian metabolites. [11,[14][15][16][17][18][19] Examples of metabolic transformations in Cunninghamella fungi are the phase I reactions hydroxylation, [14] epoxidation, [14] N-oxidation, [20] N-dealkylation, [15] O-demethylation, [15] and deamination, [15] as well as the phase II reactions glucuronic acid conjugation, [21] sulfate conjugation, [21] glucoside conjugation, [13] and riboside conjugation. [13] This fungal genus has been found to express either a cytochrome P450 [22] or a similar enzymatic system.…”
mentioning
confidence: 99%
“…doping control laboratories. Several studies have investigated the biotransformation of drugs by fungi and it has been shown that some of these organisms produce mammalian metabolites . Examples of metabolic transformations in Cunninghamella fungi are the phase I reactions hydroxylation, epoxidation, N‐oxidation, N‐dealkylation, O‐demethylation, and deamination, as well as the phase II reactions glucuronic acid conjugation, sulfate conjugation, glucoside conjugation, and riboside conjugation .…”
mentioning
confidence: 99%